PENYULUHAN TENTANG KELESTARIAN LINGKUNGAN, BAHAYA SAMPAH PLASTIK DAN PENGGUNAAN GADGET DI SELURUH SD DESA MENGESTA - Jeffrey Fernando Fallo; I P D A Prawira; I K R E Sagita; S D Wulandari; O S I Wahur; I G N W H Saputra (Universitas Muhammadiyah Tapanuli Selatan, 2020)
We want to educate the younger brothers in SD N Mengesta to use gadgets well and conducive to this counseling and socialization can give good influence to children in hopes of growing the sense of environmental care in themselves, family, peers, and the community around. Gadgets are currently a much-needed technology in society because personal devices can accelerate the work of Merka, fast in communicating, and looking for information. In addition to the means of communication, gadgets also become the need for entertainment for man itself because they can play games with only a device. Mengesta Village is one of the villages located in the Penebel sub-district, Tabanan Regency. The Program of KKN activities in Mengesta village has been carried out well thanks to the cooperation of the community, students, and the full support of the village chief Mengesta. The work program that runs during the activity is counseling and socialization about the use of plastic waste and gadgets. Plastic waste becomes a problem that nowadays gets more attention than many countries. As a material that takes a long time to decompose, plastic products will undoubtedly continue to accumulate.